2019
DOI: 10.3390/molecules24061108
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Matrine Derivatives as Novel Anti-Pulmonary Fibrotic Agents via Repression of the TGFβ/Smad Pathway

Abstract: A total of 18 matrine derivatives were designed, synthesized, and evaluated for their inhibitory effect against TGF-β1-induced total collagen accumulation in human fetal lung fibroblast MRC-5 cell lines. Among them, compound 3f displayed the most potent anti-fibrotic activity (IC50 = 3.3 ± 0.3 μM) which was 266-fold more potent than matrine. 3f significantly inhibited the fibroblast-to-myofibroblast transition and extracellular matrix production of MRC-5 cells. The TGF-β/small mothers against decapentaplegic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…In this pathway, TGF-β1 exerts biological effects through binding to type II β-β receptor and subsequently recruits and activates TGFβRI, then the activated TGFβR1 phosphorylates Smad2/3 ( 33 , 34 ). Previous studies have demonstrated that inhibiting TGFβRI significantly improves various disease, including pulmonary fibrosis ( 35 ), hypertensive nephropathy ( 36 ) and tubulo-interstitial fibrosis ( 37 ), suggesting that inhibiting TGFβRI may be a promising anti-fibrotic therapeutic strategy for DN. These findings are consistent with the current study where it was found that circRNA_0000491 knockdown inhibited TGFβ1, TGFβRI and pSmad3 protein expression levels ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, TGF-β1 exerts biological effects through binding to type II β-β receptor and subsequently recruits and activates TGFβRI, then the activated TGFβR1 phosphorylates Smad2/3 ( 33 , 34 ). Previous studies have demonstrated that inhibiting TGFβRI significantly improves various disease, including pulmonary fibrosis ( 35 ), hypertensive nephropathy ( 36 ) and tubulo-interstitial fibrosis ( 37 ), suggesting that inhibiting TGFβRI may be a promising anti-fibrotic therapeutic strategy for DN. These findings are consistent with the current study where it was found that circRNA_0000491 knockdown inhibited TGFβ1, TGFβRI and pSmad3 protein expression levels ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies found that the development of PF was related to the activation of fibroblast-to-myofibroblast transition (FMT), abnormal tissue remodeling, immune response and excessive extracellular matrix (ECM) deposition [2]. Moreover, the process of FMT is a prominent pathway leading to ECM deposition, and inhibiting the differentiation of myofibroblasts was demonstrated as an effective way to prevent PF [3,4]. Clinical studies have confirmed that drugs including hormones, non-hormone immunosuppressants, and antifibrotic, anticytokine and immunomodulatory agents, had no significant effect on the treatment of PF, and there was no effective treatment AGING found for PF patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…TCM active components have multiple targets and multiple mechanisms of pharmacological activity. Except for the above active ingredients, such as flavonoids (Baicalin [ 117 ], Hydroxysaffl [ 118 ]), terpenes (Triptolide [ 119 ], Paclitaxel [ 120 ]), glycosides (Paeoniflorin [ 121 ], Ginsenoside [ 122 ]) and alkaloids (Matrine [ 123 ], Isoliensinine [ 124 ]) also have shown different degrees of preventive or therapeutic effects on IPF, and involved multiple protective mechanisms.…”
Section: Active Components Of Tcm In the Ipf Treatmentmentioning
confidence: 99%